2022
DOI: 10.3389/fpubh.2022.986531
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of probable depression and probable anxiety, and associations with adverse childhood experiences and socio-demographics: A national survey in South Africa

Abstract: Objective and methodsMental health problems among adults are a growing public health concern, and middle-income countries such as South Africa are disproportionally affected. Using a large scale nationally representative weighted survey, we assessed the prevalence of probable depression, probable anxiety, and adverse childhood experiences (ACEs), and explored associations between probable depression, probable anxiety, ACEs, socio-economic status, and demographic characteristics.ResultsNationally, 25.7, 17.8, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 64 publications
(80 reference statements)
4
15
0
Order By: Relevance
“…Specifically, our findings show that mental health conditions are still more common in HICs and that they are rapidly increasing in LMICs, where more than a quarter of respondents reported a diagnosis of a mental health problem. These findings are in accordance with previous reports 38 , 39 . We recently conducted a national survey with weighted data representing approximately 39.6 million South African households and showed that 25.7% and 17.8% of the South African population reported moderate to severe symptoms of probable depression and anxiety, respectively 39 .…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Specifically, our findings show that mental health conditions are still more common in HICs and that they are rapidly increasing in LMICs, where more than a quarter of respondents reported a diagnosis of a mental health problem. These findings are in accordance with previous reports 38 , 39 . We recently conducted a national survey with weighted data representing approximately 39.6 million South African households and showed that 25.7% and 17.8% of the South African population reported moderate to severe symptoms of probable depression and anxiety, respectively 39 .…”
Section: Discussionsupporting
confidence: 94%
“…These findings are in accordance with previous reports 38 , 39 . We recently conducted a national survey with weighted data representing approximately 39.6 million South African households and showed that 25.7% and 17.8% of the South African population reported moderate to severe symptoms of probable depression and anxiety, respectively 39 . Furthermore, the findings that hypertension and related cardiovascular disorders (e.g., heart attack) was more prevalent in SA and Kenya than in the UK sample agrees with previous studies 40 , 41 .…”
Section: Discussionsupporting
confidence: 94%
“…The average seizure frequency over the 30 days prior to follow up was 1.5 (95%CI [0.5, 2.6]) and significantly lower than at baseline (p = 0.002). 66% of participants were No to mild depressive symptoms (0-9 points), moderate (10)(11)(12)(13)(14)(15)(16)(17)(18)(19), severe (20)(21)(22)(23)(24)(25)(26)(27) No to mild anxious symptoms (0-4 points), moderate (5)(6)(7)(8)(9)(10)(11)(12)(13)(14), severe (15)(16)(17)(18)(19)(20)(21) F I G U R E 2 Distribution of scores on the PHQ-9 (a) and GAD-7 (b) at baseline and 90-day follow up.…”
Section: -Day Follow-up Visitmentioning
confidence: 99%
“…Cross-sectional studies from multiple Sub-Saharan African countries have shown that the prevalence of depressive symptoms is high in PLWE, ranging from 40% (Ethiopia) to 86% (East Nigeria) [2]. Anxiety is also disproportionately high in PLWE and posited to be higher in Sub-Saharan African countries compared to other geographies [1,[5][6][7]. Whether these higher burdens result from a lack of access to diagnosis and treatment is not yet established.…”
Section: Introductionmentioning
confidence: 99%
“…However, some evidence shows that an estimated 9.8% of the adult population experience major (clinical) depression at some point in their life [6]. A recent large-scale, nationally representative study, assessing the prevalence of mental health problems among South African adults found that overall probable depression prevalence across South Africa varied from 14.7 to 38.8% [7].…”
mentioning
confidence: 99%